2019
DOI: 10.1038/s41467-019-12092-x
|View full text |Cite
|
Sign up to set email alerts
|

Topological kink plasmons on magnetic-domain boundaries

Abstract: Two-dimensional topological materials bearing time reversal-breaking magnetic fields support protected one-way edge modes. Normally, these edge modes adhere to physical edges where material properties change abruptly. However, even in homogeneous materials, topology still permits a unique form of edge modes – kink modes – residing at the domain boundaries of magnetic fields within the materials. This scenario, despite being predicted in theory, has rarely been demonstrated experimentally. Here, we report our o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The appearance of topologically protected gapless surface and edge states is a direct consequence of topological electron states in the bulk. In another frontier, the notion of bulk band topology has been extended to include nonelectron systems such as photonic systems [18][19][20][21][22], polaritons [23,24], phonons [25][26][27][28][29], magnons [30][31][32][33][34][35][36], magnetoelastics [37][38][39][40][41][42][43], and recently plasmons [44,45]. In all of these systems, which are described by bosonic collective modes, the band topology emanates from the nontrivial Berry curvature of the underlying Bloch wave description of bulk modes, which upon integration over the momentum space leads to an integer topological index.…”
Section: Introduction-mentioning
confidence: 99%
“…The appearance of topologically protected gapless surface and edge states is a direct consequence of topological electron states in the bulk. In another frontier, the notion of bulk band topology has been extended to include nonelectron systems such as photonic systems [18][19][20][21][22], polaritons [23,24], phonons [25][26][27][28][29], magnons [30][31][32][33][34][35][36], magnetoelastics [37][38][39][40][41][42][43], and recently plasmons [44,45]. In all of these systems, which are described by bosonic collective modes, the band topology emanates from the nontrivial Berry curvature of the underlying Bloch wave description of bulk modes, which upon integration over the momentum space leads to an integer topological index.…”
Section: Introduction-mentioning
confidence: 99%
“…Furthermore, the boundary between two 2DEGs that are magnetized along opposite directions has a gap Chern number difference equal to 2 ± and supports two unidirectional edge modes (Figure 8). The presence of these two modes, as predicted by the bulk-edge correspondence principle, was recently experimentally validated in a GaAs-AlGaAs heterostructure [78].…”
Section: Edge States On Two-dimensional Biased Plasmasmentioning
confidence: 82%
“…Recently, these properties have also been connected to topological wave physics. Specifically, it was shown that the presence of an orthogonal magnetic bias not only breaks reciprocity, but also opens a non-trivial bandgap in the bulk-mode dispersion around zero frequency, with a gap Chern number equal to 1 ± [21,78], as shown in Figure 8. The unidirectional edge modes of the magnetized 2DEG are then tied to the topological properties of the bulk-mode bandgap through the bulk-edge correspondence, and are therefore topologically protected against defects that do not close this bandgap.…”
Section: Edge States On Two-dimensional Biased Plasmasmentioning
confidence: 99%
“…This is because the neighboring ferromagnetic domains with the opposite magnetic orders perpendicular to the surface have opposite Chern numbers [1]. This domain chiral edge mode has been realized experimentally on the surface of magnetic topological insulators [39,40], and with a more controlled method with the strong permanent magnet placed atop the GaAs/AlGaAs quantum Hall heterojunction [41]. The spin modulation of the spin spiral state with one spiral period can be approximately viewed as one domain wall, and there will naturally be a chiral edge mode associated with it.…”
Section: A the Spin Spiral Casementioning
confidence: 99%